Energy politics in an uncertain world / edited by Peter Pearson - "Pearson , Peter (ed.)" (London, 1989)
Energy policy makers have always had to contend with uncertainties. However since the early 1970s both the reality and the perception of the uncertainties have grown. This is reflected in the language used to describe the major recent happenings on the energy scene, much of which conveys an impression of surprise, suddenness or violence the first, second and third oil shocks the Arab Israel and Iran Iraq Wars the Third World debt crisis the Chernobyl nuclear accident and so on.
Keywords: "Energy,"